Seminar Nasional Pendidikan Islam dalam sistem pendidikan nasiobal : risalah (Fakultas Tarbiyah, IAIN Sunan Kalijaga, 1991)
Islamic education in the program of educational system of the Islamic institutions in Indonesia: proceedings of a meeting.